Tissue transglutaminase expression in duodenal mucosa of patients with celiac disease and of normal subjects - İlyas TUNCER; İrfan BAYRAM; İsmet KABA; Rıdvan MERCAN; Serdar UĞRAŞ (Turkish Journal of Gastroenterology, 2019)
-